Incidence of Lichen Planus and Subsequent Mortality in Finnish Women - Pia Halonen; Maija Jakobsson; Oskari Heikinheimo; Mika Gissler; Eero Pukkala (Medical Journals Sweden, 2020)
The incidence pattern of lichen planus (LP) and LP-related mortality are unknown. The aim of this study was to assess these factors, based on Finnish nationwide registry data including 13,378 women with LP diagnosed during 1969 to 2012. The incidence rate for LP in 2003 to 2012 was 28 per 100,000 woman-years age-adjusted to the European Standard Population. Mortality was assessed using the standardized mortality ratio (SMR) with national mortality rates as the reference. All-cause mortality was increased (SMR 1.07, 95% confidence interval (95% CI) 1.02-1.11), with excess mortality from Hodgkin lymphoma (SMR 6.73, 95% CI 1.83-17.2), non-Hodgkin lymphoma (SMR 1.68, 95% CI 1.11-2.44), cancer of the oral cavity (SMR 10.5, 95% CI 5.99-17.0), cancer of the tongue (SMR 7.25, 95% CI 3.13-14.3), infections (SMR 1.78, 95% CI 1.14-2.64), respiratory diseases (SMR 1.31, 95% CI 1.07-1.57), and diseases of the digestive system (SMR 1.39, 95% CI 1.09-1.75). In conclusion, LP is a common disease and patients seem to have an impaired long-term prognosis.